STRATEGI PEMASARAN OBAT HEWAN SATWA UNGGUL BLITAR (Studi Kasus Di Desa Sanankulon Kecamatan Sanankulon Kabupaten Blitar) - Imam Faozi; Errythrina Vinnifera Arnyke (AVES: Jurnal Ilmu Peternakan, 2017)
The purpose of this study is to examine the marketing mix strategy that has been applied by the company in its business development, to analyze the internal and external environment condition faced by PT Satwa Unggul, to formulate the best alternative marketing strategy of PT Satwa Unggul by considering the company environment to be able to compete in the market. The data collected are primary and secondary data that are qualitative. The research method used in this study is primary data obtained from recording and direct interviews with leaders, employees, and customers. Secondary data is obtained from the report where the company jemen and literature in the form of library materials taken from previous research. The marketing mix strategy being carried out by the company concerning the product strategy (brand awareness on the brand), pricing strategy (discounted price), distribution strategy (three distribution patterns), and promotion strategy (animal inspection and free extension services) can assessed to have successfully accommodate the needs of customers with various facilities and company benefits. Based on internal environmental analysis with Descriptive Analysis can be seen that PT Satwa Unggul has a strong internal position. This means the company has been able to use its strengths and overcome its weaknesses quite well. Company's strengths include: affordable prices, good product quality, specialized workforces, sales with personal selling, and sales targets for large farmers. While the weakness of the company in the form: strong influence of leadership, capital limitations, delay in delivery time, no exclusive contract with customers, and the absence of R & D activities. Based on the analysis of the external environment with Descriptive Analysis, it can be seen that PT Satwa Unggul also has a strong external position, because it has been able to take advantage of opportunities and can handle the threat quite well .keyword : marketing strategy, satwa unggul, analyze